(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Cirrhosis with its complication is a major health concern in Pakistan. Endoscopy is an invasive and expensive modality for screening for esophageal varices which is one of the most common complication of liver cirrhosis. Research is being conducted to explore non-invasive markers that can replace this invasive technique. We aimed to evaluate the predictive value of the ratio of the size of the right lobe of liver to serum albumin concentration in prediction of the presence of esophageal varices. Methods: It was a cross-sectional study conducted at the Medicine Department, Ghurki Trust Teaching Hospital, Lahore from January 4 till July 31. The study included 297 patients of all the genders, aged 20-70 years, diagnosed cases of liver cirrhosis for at least 6 months and having suspected esophageal varices on right liver lobe size to serum albumin ratio >4.1. All the patients were subjected to upper GI endoscopy to confirm predicted varices. Data was analyzed using SPSS 23.0. PPV of the ratio was calculated. Post-stratification chi square was used to find association (p value <0.05 as significant). Results: The patients had a mean age of 51.5 ± 9.2 years with 180 (60.6%) male and 117 (39.4%) female patients. Diagnosis of esophageal varices was confirmed in 225 (75.8%) patients on endoscopy. There were 225 true positive and 72 false positive cases. Positive predictive value was 75.8%. Conclusion: The positive predictive value of the ratio of the size of the right liver lobe to serum albumin was statistically significant in predicting the presence of esophageal varices on upper GI endoscopy. These findings were not dependent on the patient’s age, BMI, gender, duration of disease or serum bilirubin level. Cirrhosis, Esophageal Varices, Right Liver Lobe Diameter to Serum Albumin Ratio